(untitled) (Tempo e Argumento, 2021)
The article analyzes the auditorium of the Health and Public Assistance Secretary of Minas Gerais as a place of memory for workers. In 1961, the auditorium of the Secretary of Heath hosted the 1st National Congress of Agricultural Workers and, in 1962, the 1st Congress of Favelado Workers in Belo Horizonte, being one of the places in the urban space identified with the social protest of workers. The connection between the two events that expressed the position of agricultural workers and favelados workers in the protest cycle of the basic reform, and the relationship between agrarian and urban reform are explored in the article. Keywords: basic reform; urban and rural workers; social memory.